GTP cyclohydrolase drives breast cancer development and promotes EMT in an enzyme-independent manner - Wang, Z; Zhang, N; Zhang, M; Jiang, Y; Fischer, R; Ng, AS; Bridges, E; Zhang, W; Zeng, X; Luo, Q; Liang, J; Győrffy, B; et al. (American Association for Cancer Research, 2023)
GTP cyclohydrolase (GCH1) is the rate-limiting enzyme for tetrahydrobiopterin (BH4) biosynthesis. The catalysis of BH4 biosynthesis is tightly regulated for physiological neurotransmission, inflammation, and vascular tone. Paradoxically, BH4 has emerged as an oncometabolite regulating tumor growth, but the effects on tumor development remain controversial. Here, we found that GCH1 potentiated the growth of triple-negative breast cancer (TNBC) and HER2+ breast cancer and transformed nontumor breast epithelial cells. Independent of BH4 production, GCH1 protein induced epithelial-to-mesenchymal transition by binding to vimentin (Vim), which was mediated by HSP90. Conversely, GCH1 ablation impaired tumor growth, suppressed Vim in TNBC, and inhibited EGFR/ERK signaling while activating the p53 pathway in estrogen receptor-positive tumor cells. GCH1 deficiency increases tumor cell sensitivity to HSP90 inhibition and endocrine treatments. In addition, high GCH1 correlated with poor breast cancer survival. Together, this study reveals an enzyme-independent oncogenic role of GCH1, presenting it as a potential target for therapeutic development. Significance GTP cyclohydrolase functions as an oncogene in breast cancer and binds vimentin to induce epithelial-to-mesenchymal transition independently of its enzyme activity, which confers targetable vulnerabilities for developing breast cancer treatment strategies.